Greek Upper Primary Grade Students’ Images About Science and Scientists: An Alternative Descriptive Piece of the Puzzle - Chionas, Georgios; Emvalotis, Anastassios (Frontiers in Education, 2022)
This study examined the perceptions of upper primary grade level students about science, scientists, and their work. Participants were 284 fifth- and sixth- grade students (aged 10-12) from six urban areas of Attica (Greece). An open-ended questionnaire was employed for data selection. Students’ responses were analyzed both qualitatively (through thematic analysis) and quantitatively. The findings suggest that the participants in this study hold distinct perceptions of what science is, who a scientist is, and how science is done. Although most students referred to science and scientists in a positive light, our findings suggested that they held traditional and narrow perceptions of such issues (e.g. a scientist is a brilliant, talented person who works in Natural Sciences, science is a contributor to human welfare or it is a product). Our data also suggested that the students could not make a clear distinction between science and technology, concepts that were used interchangeably in our study. Educational implications that may help breaking these naïve perceptions were discussed.